Peran Guru Kristen Sebagai Penuntun Untuk Meningkatkan Numerasi Siswa - Fetty Hosanna Sigalingging; Henni Sitompul (Diligentia: Journal of Theology and Christian Education, 2024)
The low numeracy of students is still an emerging topic of discussion and has not yet made progress. Research from PISA and OECD shows that Indonesia ranks low for numeracy skills. Many efforts have been made to improve numeracy, one of which is the implementation of the Christian teacher's role as a guide. Therefore, this article is written with the aim of examining the role of Christian teachers as guides to improve student numeracy. This research was conducted using a literature review. The Christian teacher as a guide means that the teacher plays a role in directing and providing guidance for students. In improving numeracy, Christian teachers play a role in directing students to the right mindset towards numeracy content. Christian teachers make Jesus as a shepherd an example in carrying out their role as a guide to improve numeracy. Christian teachers help students to improve numeracy according to numeracy indicators while keeping the Bible as the source of truth. Christian teachers will make Christ the center of education, which means that all aspects of education are worked on and focused on Christ. Thus students can utilize numeracy skills in accordance with biblical truth and glorify God. Future researchers are advised to examine more deeply the factors that influence numeracy and find solutions to the appropriate role of Christian teachers to improve numeracy skills.BAHASA INDONESIA ABSTRACTRendahnya kemampuan berhitung siswa masih menjadi perbincangan yang muncul dan belum mengalami kemajuan. Penelitian dari PISA dan OECD menunjukkan bahwa Indonesia berada di peringkat rendah untuk kemampuan berhitung. Banyak upaya yang telah dilakukan untuk meningkatkan kemampuan berhitung, salah satunya adalah dengan menerapkan peran guru Kristen sebagai penuntun. Oleh karena itu, artikel ini ditulis dengan tujuan untuk mengkaji peran guru Kristen sebagai penuntun untuk meningkatkan kemampuan berhitung siswa. Penelitian ini dilakukan dengan menggunakan studi literatur. Guru Kristen sebagai penuntun berarti guru berperan untuk mengarahkan dan memberikan tuntunan kepada siswa. Dalam meningkatkan kemampuan berhitung, guru Kristen berperan dalam mengarahkan siswa agar memiliki pola pikir yang benar terhadap materi berhitung. Guru Kristen menjadikan Yesus sebagai gembala sebagai teladan dalam menjalankan perannya sebagai penuntun untuk meningkatkan kemampuan berhitung. Guru Kristen menolong siswa untuk meningkatkan kemampuan berhitung sesuai dengan indikator-indikator berhitung dengan tetap menjadikan Alkitab sebagai sumber kebenaran. Guru Kristen akan menjadikan Kristus sebagai pusat dalam pendidikan, yang berarti semua aspek pendidikan dikerjakan dan difokuskan pada Kristus. Dengan demikian siswa dapat menggunakan kemampuan berhitung sesuai dengan kebenaran Alkitab dan memuliakan Tuhan. Peneliti selanjutnya disarankan untuk meneliti lebih dalam lagi mengenai faktor-faktor yang mempengaruhi kemampuan berhitung dan mencari solusi mengenai peran guru Kristen yang tepat untuk meningkatkan kemampuan berhitung.